G257(P) An overseas diploma in child health (dch) clinical training course and assessment programme-lessons learned. (27th April 2015) - Mathew, A; Venugopalan, P; Crane, D
Abstract : Introduction and aim: Undergraduate and postgraduate education and training differ across nations in the emphasis placed on the knowledge, skills and attitudes within the training curriculum. In the DCH (UK) clinical examination, candidates are assessed in all areas of the doctor-patient interaction; skills in communication, proficiency in all areas necessary for a comprehensive assessment and management of the patient have to be demonstrated. This abstract describes the experience of doctors who participated in the first overseas RCPCH DCH (UK) clinical training course and pilot examination. Methods: 5 UK faculty members supported by 5 Indian faculty members delivered a 2-day DCH (UK) training course and pilot assessment in India. 32 candidates attended, the target number set by the RCPCH. On day-1, training was provided around the stations in the examination circuit and feedback sought utilising a questionnaire survey represented on a scale of 1–5, 1 indicating very poor, 5 indicating excellent. Averaged scores are displayed graphically (Figure1 ). On day-2, a pilot examination was held, and feedback sought through a questionnaire survey utilising a 7-point Likert scale (Figure 2 ). Free text comments were invited on both days (Table 1). Results: 29 of the 32 candidates provided feedback on day 1, 31 of the 32 on Day 2. Candidates expressed deep appreciation of this experience of teaching and training. They emphasised a desire to have further training, in all aspects of the course, stressing the importance for more-time and patient contact per session. They appreciated the different emphasis placed in UK postgraduate training, where communication, an empathetic approach, and good clinical examination and interpretive skills are the core skills assessed in our examination. The collaborative, supportive and welcoming approach displayed by the faculty of examiners was also widely appreciated. Conclusion: The results obtained from this course provide evidence that such teaching and training is highly valued; with expressions of interest for further training. Pertinent feedback around how to improve future courses will be considered carefully and addressed in order to develop a sustainable overseas programme.